A collaborative inventory model for vendor-buyer system with stochastic demand, defective items and carbon emission cost. Issue 2 (2018) - Jauhari, Wakhid Ahmad
This paper develops a joint economic lot-sizing problem (JELP) involving of a vendor and a buyer under defective products. The vendor's production process is assumed to be imperfect, hence the lot delivered to the buyer may contain a certain number of imperfect products with known probability density function. The carbon emissions are considered in the model and are calculated from both transportation and production activities. The model also considers a situation in which the vendor has an opportunity to adjust the production rate. The objective of the model is to minimise total cost by simultaneously determining the shipment size, number of deliveries, production rate and safety factor. An iterative procedure is suggested for solving the model. Numerical examples are used to illustrate the application of the model.